O processo de metropolização em Sorocaba e sua hinterlândia: análise a partir dos eixos de desenvolvimento - Garramona, Rofecele Teixeira (Universidade Federal de São Carlos, 2023)
Brazilian urban space has become the target of studies regarding metropolitan dynamics in the current period, where we consider that it is now equipped with new artifacts that give it characteristics never seen before, such as the change in focus on the economy, passing from the secondary to the tertiary sector and the intense circulation of information, capital, products and people, which begin to require new structures and dictate new rhythms in these spaces. The metropolitan phenomenon becomes the target of public policies that distort its main characteristics, where we notice a growing number of locations considered metropolitan in the legislative sphere, but which do not come close to these attributes in their daily lives, and let the priority of state interests appear in the issue of planning and territorial ordering, leaving open an extensive margin for the legislative power to dictate the rules of what would be the constituent municipalities of a metropolitan region. In our research we will analyze the case of Sorocaba and its neighboring municipalities, verifying whether there is an integration relationship between them through the phenomena of conurbation, circulation routes (necessary to support the flow of people and goods) and public and private structures that characterize the involvement of this specific region with the metropolization process.
The metropolization process in Sorocaba and its hinterland: analysis based on development axes
Keywords: Planejamento regional e urbano; Metropolização; Integração regional; Regional and urban planning; Metropolization; Regional integration; CIENCIAS HUMANAS::GEOGRAFIA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA